2015
DOI: 10.2166/wst.2015.341
|View full text |Cite
|
Sign up to set email alerts
|

Application of forward osmosis (FO) under ultrasonication on sludge thickening of waste activated sludge

Abstract: Forward osmosis (FO) is an emerging process for dewatering solid-liquid stream which has the potential to be innovative and sustainable. However, the applications have still been hindered by low water flux and membrane fouling when activated sludge is used as the feed solution due to bound water from microbial cells. Hence, a novel strategy was designed to increase sludge thickening and reduce membrane fouling in the FO process under ultrasonic condition. The results from the ultrasound/FO hybrid system showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…Ultrasonic application also reduced the extent of concentration polarisation by rapidly mixing both the feed and draw solutions close to the membrane surface, and thus improving the water flux dynamics [50]. Our results are consistent with previous studies on membrane cleaning using ultrasonication [42,43,51].…”
Section: Parametersupporting
confidence: 91%
See 2 more Smart Citations
“…Ultrasonic application also reduced the extent of concentration polarisation by rapidly mixing both the feed and draw solutions close to the membrane surface, and thus improving the water flux dynamics [50]. Our results are consistent with previous studies on membrane cleaning using ultrasonication [42,43,51].…”
Section: Parametersupporting
confidence: 91%
“…FO membrane fouling can be controlled via either a physical or chemical cleaning process [38,39]. Physical cleaning techniques such as cross-flow velocity increase or pulsated crossflow, membrane flushing, air-scouring, osmotic backwashing, and ultrasonication have been studied for different applications and FO configurations [40][41][42][43]. These techniques provide vigorous hydrodynamic conditions to prevent or remove the fouling cake layer from the membrane surface [30,40].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the potential of FO to treat many complex feed solutions has been demonstrated in the literature. These complex solutions include drilling and fracking fluids from oil and gas exploration [6][7][8][9] , sludge 10,11 , digested sludge centrate 2,12,13 , and municipal wastewater 4,14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Ansari et al 12 has recently demonstrated a seawater-driven FO process for phosphorus recovery from digested sludge centrate with a specific focus on evaluating the efficiency of nutrient recovery. Results from previous studies suggest that identifying the most suitable membrane type and orientation is necessary to ensure the best performance of seawaterdriven FO process for pre-concentrating sludge centrate 2,[10][11][12] . More importantly, understanding of the fouling process and developing strategies to control fouling need to be discussed to guarantee the long-term operation of the FO system.…”
Section: Introductionmentioning
confidence: 99%